Innovation of Science Teaching Material Based on STEM-PjBL in the Implementation of the Merdeka Curriculum - Nurcahyo, Muhammad Aqmal; Afryaningsih, Yunika (Journal of Innovative Science Education, 2024)
The learning process of Natural and Social Sciences (IPAS) requires adequate teaching materials and integrated with innovative approaches to make learning more interesting, practical, and fun. The integration of the STEM-PjBL approach can be an option in the development of teaching materials because it encourages students to develop process skills through real problem-solving-based learning, practicum implementation, and project activities. This study aims to produce IPAS teaching materials that are in accordance with the content of science based on STEM-PjBL for phase C of grade V thus supporting the implementation of the Merdeka curriculum and improving process skills as an integral part of science learning. The development method used is the Analysis, Design, Development, Implementation, Evaluation (ADDIE) model. Validation of teaching materials was carried out by media experts with a match rate of 88% (very feasible), material experts at 83% (very feasible), and language experts at 82% (very feasible). Additionally, small group trials with students resulted in an 80.14% (good), suggesting that the materials are engaging and effective. The integration of STEM-PjBL supports the implementation of the Merdeka curriculum, emphasizing the development of students' process skills through real-world problem-solving, practical activities, and projects. Given the high feasibility ratings from experts and positive feedback from students, the developed science teaching materials have the potential to be widely adopted in grade V, improving the overall science learning experience. Future research should explore long-term impacts, comparative effectiveness, teacher training, technological integration, and broader demographic studies. These materials enhance learning experiences, support the Merdeka curriculum, improve process skills, provide valuable teacher resources, and can inform educational policy.